Land and Credit Mortgages in the Medieval and Early Modern European Countryside (Palgrave Studies in the History of Finance,, 2018)
This volume investigates the use of mortgages in the European countryside between the thirteenth and eighteenth centuries. A mortgage allowed a loan to be secured with land or other property, and the practice has been linked to the transformation of the agrarian economy that paved the way for modern economic growth. Historians have viewed the mortgage both positively and negatively: on the one hand, it provided borrowers with opportunities for investment in agriculture; but equally, it exposed them to the risk of losing their mortgaged property. The case studies presented in this volume reveal the variety of forms that the mortgage took, and show how an intricate balance was struck between the interests of the borrower looking for funds, and those of the lender looking for security. It is argued that the character of mortgage law, and the nature of rights in land in operation in any given the place and period, determined the degree to which mortgages were employed. Over time, developments in these factors allowed increasing numbers of peasants to use mortgages more freely, and with a decreasing risk of expropriation. This volume will be appealing to academics and researchers interested in financial history, rural credit and debt, and the economic history of agrarian communities.